Віртуальне дослідження параметричних випробувань відцентрового насоса - Василенков, В. Є.; Гудзенко, М. М.; Наземцев, О. І. (Energy and Automation, 2017)
Virtual RESEARCH parametric tests of Centrifugal pumps V. Vasilenkov, M. Gudzenko, A. NazemtsevAnnotation. The possibility of the use of simulation in hydraulics on the example of laboratory work "Parametric tests of the centrifugal pump". The results of the study parametric virtual testing of a centrifugal pump and a graphical display is given. Key words: centrifugal pump, parametric trials, virtual research, pressure, expenditure